Implementing buprenorphine for opioid use disorder in veterans health administration primary care: a qualitative analysis - Aline Lott; Anissa N. Danner; Carol A. Malte; Hope A. Salameh; Diana Bachowski; Adam J. Gordon; Hildi J. Hagedorn; Madeline C. Frost; Emily C. Williams; Andrew J. Saxon; Ryan S. Trim; Eric J. Hawkins (Addiction Science & Clinical Practice)
Abstract Background Medications for opioid use disorder are evidence-based, guideline-recommended treatments. While buprenorphine can be prescribed in nonspecialized office-based settings, it is underutilized. Using a multifaceted implementation initiative, the Veterans Health Administration (VHA) sought to expand access to buprenorphine in nonspecialized office-based settings, including primary care clinics. The purpose of this qualitative evaluation was to assess and describe primary care clinicians’ perspectives on delivering buprenorphine care during the first year of the initiative. Methods Using a snowball sampling approach, individualized emails were sent to primary care clinicians participating in a VHA initiative (n = 43) inviting them to be interviewed. Individual semi-structured interviews were conducted September 2019 through January 2020, and were audio-recorded, transcribed, and analyzed using thematic analysis. The Consolidated Framework for Implementation Research (CFIR), a meta-theoretical framework of five domains associated with successful adoption of interventions, was used to organize findings. Results Of 43 clinicians invited, 19 responded and were interviewed (44.2%). Findings represented two CFIR domains: Inner Setting and Characteristics of Individuals. For Inner Setting, three themes were identified as influencing implementation during the first year of the initiative. Clinicians reported a shared receptivity to implement buprenorphine, organizational support from pharmacy services and leadership, as well as cohesive relationships among implementation team members and collaboration with outside clinics. Noted barriers included fit within primary care workflows and lack of staff, time and access to onsite laboratory services and buprenorphine. For Characteristics of Individuals, two themes were identified that may facilitate clinicians’ willingness to provide buprenorphine care. Namely, clinicians reported positive attitudes about and experiences delivering opioid use disorder care and a willingness to learn/do something new. Conclusions While implementation strategies should be tailored to individual clinic needs, prioritizing factors identified in this evaluation may support successful implementation of buprenorphine delivery in primary care.